Synthesis and Antibacterial Activity of Epoxides Derived from Chalcones - Husain, Asif; Shaharyar, Mohd. (Asian Journal of Chemistry, 2016)
Epoxides (IIa-e) have been synthesized by reacting appropriate chalcones with hydrogen peroxide. These epoxides were reacted with aniline in presence of boron-trifluoride in order to prepare some new dihydroxy compounds (IIIa-e); however, these compounds could not be separated in pure form. The epoxides were screened for antibacterial activity.